2018
DOI: 10.2147/ppa.s175474
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy among HIV/AIDS patients in the context of early treatment initiation in Vietnam

Abstract: PurposeThis study aimed to assess the antiretroviral therapy (ART) compliance among patients with HIV/AIDS and its associated factors in the context of universal ART initiation in Vietnam.Patients and methodsA cross-sectional survey was conducted in five ART clinics located in three provinces, such as Hanoi, Thanh Hoa, and Lao Cai, from July to September 2017. Overall, adherence to ART in the last month was measured using a 100-point Visual Analog Scale (VAS). Besides, information about forgetting doses in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…One of the targets of the UNAIDS Fast Track approach to accelerate actions to end the AIDS epidemic is the 95-95-95 initiative, which seeks to achieve viral suppression in 95% of PLHIV taking ART (4). These targets are a revision of the 2014 90-90-90 targets which sought to ensure that by the end of that period, 90% of PLHIV know their status and 90% of PLHIV who their status are on ART, while 90% of those on therapy are virally suppressed However, such a target of viral suppression among PLHIV requires a sustained high level of adherence (> 95%) to ART in managing HIV as a chronic disease, with the aim of ending the AIDS epidemic by 2030 (2,(5)(6)(7)(8)(9). UNAIDS data showed that Ghana's performance as at 2019 per the UNAID's target was 58-45-31, showing how far the country is towards achieving the goal of ending AIDS by 2030 (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the targets of the UNAIDS Fast Track approach to accelerate actions to end the AIDS epidemic is the 95-95-95 initiative, which seeks to achieve viral suppression in 95% of PLHIV taking ART (4). These targets are a revision of the 2014 90-90-90 targets which sought to ensure that by the end of that period, 90% of PLHIV know their status and 90% of PLHIV who their status are on ART, while 90% of those on therapy are virally suppressed However, such a target of viral suppression among PLHIV requires a sustained high level of adherence (> 95%) to ART in managing HIV as a chronic disease, with the aim of ending the AIDS epidemic by 2030 (2,(5)(6)(7)(8)(9). UNAIDS data showed that Ghana's performance as at 2019 per the UNAID's target was 58-45-31, showing how far the country is towards achieving the goal of ending AIDS by 2030 (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, barriers to ART still remain among developing countries. Barriers include the socio-economic status of patients including unemployment, poverty, food insecurity, distance to clinics and transportation costs, human resource constraints, healthcare provider practices such as inadequate counselling sessions, abuse of patient confidentiality, stigma, depression and medicine stock-outs (7)(8)(9)(10)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the VAS is depicted as a 10 cm long horizontal line, marked in 5 cm increments from 0 to 100. The participants had to mark their adherence levels for the past 30 days on a line chart, which included taking the medication at the right time and dose as prescribed [ 21 ]; any score below 95% was considered as suboptimal adherence or non-adherence [ 22 ]. This tool has been extensively utilized in low- and middle-income nations and has demonstrated significant (r = 0.5–0.7) correlations with other self-reported assessments, objective pill counts, electronic drug monitors (EDMs), and viral loads.…”
Section: Methodsmentioning
confidence: 99%
“…A proper antiretroviral therapy is the most effective way to increase the life expectancy of HIV patients. This treatment reduces mortalities, morbidities and opportunistic infections and prolongs survival (Mai et al, 2018). Patients with HIV virus will get AIDS symptoms without ART.…”
Section: Introductionmentioning
confidence: 99%